Influence of Project Teams on Performance of Nairobi County Government Health Center Projects in Kenya - Kemuma, Ochwando; Lango, Benard (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: The aim of the study was to examine the influence of project teams on performance of Nairobi County Government health centre projects in Kenya. Methodology: This study will use of a descriptive research design. The study will target 15 completed healthcare projects byNMS. The target population for the study will therefore be 399 project management employees. The sample size will be derived from the target population using Yamane's sample size determination formula. 1.9975. The 200 respondents will be chosen with the help of stratified random sampling technique. The study's primary data will be obtained using semi-structured questionnaires. Quantitative and qualitative data will be generated from the closed-ended and open-ended questions, respectively. Qualitative data will be analyzed on thematic basis and the findings provided in a narrative form. Inferential and descriptive statistics will be employed for analysis of quantitative data with the assistance of Statistical Package for Social Sciences (SPSS version 25). The study results will be presented through use of tables and figures. Findings: The study revealed that there was a significant relationship between project team communication and performance and Nairobi County health projects. It was further concluded that the size of the project team membership is effective and team members are constituted based on skills and abilities. The study also found that team members have order and ranks and formal organization never gets the way on how the job gets done. There is a policy framework that guides the formation of project team in the county and the project team has a clear vision. It was also showed that project team has a clear mission and the project team has a clear definition of the task to be performed. It was also concluded that project team development contributes to the productivity of the employees and training contributes to the development of project teams. Unique Contribution to Theory, Practice and Policy: The study was anchored on the human capital theory which was developed by Schutz (1961) and the theory of constraints which was propounded by created by Eliyahu Goldratt in 1984. It is recommended to establish a well-defined project structure with clearly defined roles, ensuring that each team member understands their responsibilities and how they contribute to the overall project goals. Regular communication and updates on roles and responsibilities should be maintained throughout the project lifecycle. It also recommended that project team should be comprise people with skills, expertise and diversity.